2010
DOI: 10.1007/s10600-010-9525-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of N(12)-(2-hydroxy-2-phenylethyl)cytisine

Abstract: 547.94 S. P. Ivanov, L. V. Spirikhin, and V. A. Dokichev* Diastereomers of N(12)-(2-hydroxy-2-phenylethyl)cytisine were synthesized by reduction of N(12)-(2-oxo-2-phenylethyl)cytisine by Yamamoto reagent. Their structures were solved using x-ray structure analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Various studies report modern methods for the synthesis of cytisine (Bara ´t et al, 2018;Hirschha ¨user et al, 2011;O'Neill et al, 2000;Pe ´rez et al, 2012) or cytisine modification (Brel, 2016;Kulakov et al, 2010;Kulakov & Nurkenov, 2012;Shishkin et al, 2010;Marrie `re et al, 2000;Frasinyuk et al, 2007). From the large number of cytisine derivatives, substances with biological activity (Tutka et al, 2019;Gotti & Clementi, 2021;Liu et al, 2020) and agents used in medicine (Tabex) have been found.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Various studies report modern methods for the synthesis of cytisine (Bara ´t et al, 2018;Hirschha ¨user et al, 2011;O'Neill et al, 2000;Pe ´rez et al, 2012) or cytisine modification (Brel, 2016;Kulakov et al, 2010;Kulakov & Nurkenov, 2012;Shishkin et al, 2010;Marrie `re et al, 2000;Frasinyuk et al, 2007). From the large number of cytisine derivatives, substances with biological activity (Tutka et al, 2019;Gotti & Clementi, 2021;Liu et al, 2020) and agents used in medicine (Tabex) have been found.…”
Section: Chemical Contextmentioning
confidence: 99%